Mobile Apps Usefulness, Perceived Enjoyment, Trust dan Perceived Benefit terhadap Intention to Purchase Decisions Indonesian Street Food di Jakarta - Jaya Chandra; Vita Briliana (Jurnal Bisnis dan Akuntansi, 2021)
The purpose of this study was to determine the effect of mobile apps usefulness, perceived enjoyment, trust, and perceived benefit on the intention to purchase decisions of Indonesian street food in Jakarta. The research design used descriptive research and causality research, where the variables were measured with intervals (1-5) or Likert Scale. This study uses primary data collected by questionnaire. Sampling in this study was purposive sampling and used 211 respondents. The results of this study indicate that perceived enjoyment and perceived benefit have an influence on attitude, attitude and trust have an influence on intention to purchase decisions. While mobile apps usefulness has no effect on attitude.